Using STELLA simulation models to teach natural resource economics. Issue 1 (2nd January 2016) - Dissanayake, Sahan T. M.
Abstract: In this article, the author discusses how graphical simulation models created using STELLA software can be used to present natural resource systems in an intuitive way in undergraduate natural resource economics classes based on his experiences at a leading research university, a state university, and a leading liberal arts college in the United States. The models allow students to develop an intuitive understanding of the economic aspects of natural resource systems. The author provides a short introduction to STELLA and then presents an economic model of the fishery in detail as an example of how models can be used in a classroom. He then discusses how he incorporates STELLA into his natural resource economics course, and closes the article by comparing STELLA with alternate methods.